(untitled) (Research, Society and Development, 2023)
This narrative bibliographical article invites academics and psychology professionals to reflect and contextualize their practice in a field of activity that grows according to human evolution and permeates it: disaster and emergency situations. In order to assign meaning to their practice based on who is affected by it, this article aims to reflect and identify possible conduct that professionals can adopt as part of their practice. Therefore, it is necessary to emphasize some guidelines that contribute to action in this field, being them the ethical conduct of the professional, the understanding of the dynamics of human suffering and psychological counseling, where such procedures are directly linked to the subject’s core, which enables a greater support for the construction of the psychologist’s practice in the face of disaster and emergency situations. Nevertheless, without the idealization of parameters that can support their practice, there is a lack of dialogue on the topic, which leads to a lack of interest among professionals in the field, precisely because they do not understand what structures their own practice. In this way, interventions need to be articulated with a focus on maintaining the life and health of suffering human beings, ensuring attention to their basic needs and possibilities for restructuring their lives.